Asperization of dental cavity to maximize the adhesion of composite resin restorations in patients with noncarious cervical lesions [NCCL] using a self-etch adhesive system: double blind randomized clinical trial - Antunes , André Maico (2019)
Objectives: Evaluate clinically the longevity of composite resin restorations of patients with non-carious cervical lesions (NCCL), which was asperized to maximize adhesion of a universal adhesive system used in the self-etching mode for up to 12 months. A double-blind, split-mouth randomized clinical trial was performed on 31 volunteers, over 18 years of age, with at least two NCCLs with a maximum of 50% enamel margin, regardless of their location in the dental arch, with adequate oral hygiene, absence of periodontal disease, without active caries lesions and parafunctional habits, had at least 20 functioning teeth, absence of active staples of removable partial dentures in the teeth included in the research, totalizig 109 restorations. A paired randomization was performed to select the teeth per patient that were part of each experimental group. The group 1 (SE) and group 2 (SEa), before the application of the adhesive system, the cavity was asperized with a spherical diamond bur FG1014 (KG Sorosen, Cotia, SP, Brazil) at high speed under refrigeration with soft pressure for 5 seconds. The clinical evaluation method used was (FDI) and (USPHS) criteria. Restoration retention was assessed as the primary outcome within the functional properties. The other clinical parameters evaluated, among the aesthetic properties were: marginal discoloration; corresponding to the functional properties: marginal adaptation; and on biological properties: caries lesion adjacent to restoration and postoperative sensitivity. The data were submitted to descriptive statistical analysis of variance by Friedman (α = 0.05) and their performance at different moments will be evaluated by the Mc Nemar test (α = 0.05) Results: 16 restorations were lost after 12 months (6 for the SE group and 10 for the SEa group). Marginal discoloration occurred in 1 (SEa) and 14 (5 SE and 9 SEa) of the restorations evaluated, respectively, for the USPHS and FDI criteria. Four restorations (1 SE and 3 SEa) were classified as bravo for marginal adaptation using the USPHS criteria and 18 restorations (7 SE and 11 SEa) when the FDI criteria were applied. Postoperative sensitivity was 2 teeth from SE to FDI and 1 tooth to SE (USPHS), and no case of recurrent caries was found in the study. Clinical Relevance: With the limitations of this study it was concluded that the asperization didn’t improve the results of adhesion to fracture and retention.